Pengaruh Biochar Kulit Buah Kakao dan Berbagai Agens Hayati Terhadap Pertumbuhan Bibit Kakao - Arham, Arham; Bahrun, Andi; Karimuna, La; Rakian, Tresjia Corina; Gusnawaty H.S., Gusnawaty H.S. (Universitas Halu Oleo, 2020)
The use of cocoa pod husk biochar and various biological agents in the planting medium significantly increased the growth of cocoa seedlings. The research was conducted using a Randomized Block Design (RBD) with a Split Plot pattern. The main factors consisted of 2 (two) treatment levels, namely: B0 (without biochar of cocoa pod skin) and B1 (15 g of cocoa pod husk biochar), while the child factors consisted of 4 (four) treatment levels, namely: A0 (without biological agents), M (arbuscular mycorrhiza 15 g), MR (arbuscular mycorrhizae 15 g + 15 ml rhizobacteria) and MT (arbuscular mycorrhizae 15 g + Trichoderma sp. 15 ml), so that there are 8 (eight) treatment combinations, namely: B0A0 (without biochar and without biological agents), B0M (without cocoa pod husk biochar + arbuscular mycorrhizae 15 g), B0MR (without cocoa pod husk biochar + arbuscular mycorrhizae 15 g + rhizobacteria 15 ml), B0MT (without cocoa pod husk biochar + arbuscular mycorrhiza 15 g + Trichoderma sp. 15 ml), B1A0 (cocoa pod husk biochar 15 g + without biological agents), B1M (cocoa pod husk biochar 15 g + arbuscular mycorrhizae 15 g), B1MR (cocoa pod husk biochar 15 g + arbuscular mycorrhizae 15 g + rhizobacteria 15 ml), B1MT (cocoa pod husk biochar 15 g + arbuscular mycorrhizae 15 g + Trichoderma sp. 15 ml), which repeated 4 (four) times so that there are 32 experimental units. The variables observed were plant height, total leaf area, number of leaves, root length, root dry weight, shoot dry weight. The results showed that the interaction of cocoa pod husk biochar and biological agents had no significant effect on the growth of cocoa seedlings. Application of cocoa pod husk biochar 15 g/polybag had a significant effect in increasing the growth of cocoa seedlings compared to without cocoa pod husk biochar, while the application of biological agents was shown in the 15 g arbuscular mycorrhizae + Trichoderma sp. 15 ml / polybag has a very significant effect on increasing the growth of cocoa seedlings compared to without biological agents.Keywords: Biochar, arbuscular mycorrhizal, nutrient uptake.